The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2003
DOI: 10.1590/s1413-70542003000500006
|View full text |Cite
|
Sign up to set email alerts
|

Heterose e capacidade combinatória de linhagens de pimentão (Capsicum annuum L.)

Abstract: Conduziu-se este trabalho com os objetivos de avaliar a capacidade combinatória de linhagens-elite de pimentão, identificar combinações híbridas superiores quanto à produtividade e qualidade de frutos, e inferir sobre os modos de ação gênica envolvidos na expressão dos caracteres de importância econômica. Para isso, foram realizados cruzamentos dialélicos para obtenção de híbridos, os quais foram analisados segundo o esquema dialélico parcial tipo North Carolina II, estimando-se as capacidades geral (CGC) de c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
6

Year Published

2009
2009
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
1
5
0
6
Order By: Relevance
“…The higher genetic divergence among some Murupi landraces suggests there being a possibility for a significant heterotic effect in their crossings, enhancing the agronomical characters such as sweet pepper (C. annuum) (Gomide et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…The higher genetic divergence among some Murupi landraces suggests there being a possibility for a significant heterotic effect in their crossings, enhancing the agronomical characters such as sweet pepper (C. annuum) (Gomide et al, 2003).…”
Section: Resultsmentioning
confidence: 99%
“…Nesse trabalho, em geral, os cruzamentos com estimativas elevadas e favoráveis para CEC não associaram estimativas também favoráveis para CGC indicando que além dos efeitos aditivos os não-aditivos são também importantes, corroborando com os resultados de Tavares et al (1997), Patel et al (1998), Maluf et al (1999, Mamedov e Pyshnaja (2001), Doshi et al (2001) e Gomide et al (2003). Esse resultado demonstra que quando o objetivo é a obtenção de híbridos superiores a partir de um grupo de linhagens contrastantes, as estimativas de CGC são de relativa importância.…”
Section: Prodt (T Haunclassified
“…Al respecto, Gutiérrez et al (2002) reportan que a medida que la divergencia genética de los materiales se incrementa, values of ACG than values of ACE, similar to that found by Gomide et al (2003) and contrary to that reported by Sánchez et al (2011) in squash Grey Zucchini, where he found that dominance variance was more important for the major yield components (fruits per plant, fruit length and yield per plant) than additive variance.…”
Section: Resultados Y Discusión Análisis De Varianza Combinadomentioning
confidence: 80%